Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.jtbi.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

A numerical model suggests the interplay between nuclear plasticity and stiffness during a perfusion assay

Abstract: Cell deformability is a necessary condition for a cell to be able to migrate, an ability that is vital both for healthy and diseased organisms. The nucleus being the largest and stiffest organelle, it often is a barrier to cell migration. It is thus essential to characterize its mechanical behaviour. First, we numerically investigate the visco-elasto-plastic properties of the isolated nucleus during a compression test. This simulation highlights the impact of the mechanical behaviour of the nuclear lamina and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…In line with our previous works (Allena and Aubry 2012;Deveraux et al 2017), we propose a continuum finite elements model to simulate cell behaviour over the flat and micropatterned substrates coated with adhesive fibronectin. As mentioned above, our main objective is to depict the nucleus self-deformation as a function of the micropillared substrate geometry and the actin network around the nucleus itself.…”
Section: Modelling Of Cell-substrate Interactionmentioning
confidence: 64%
See 2 more Smart Citations
“…In line with our previous works (Allena and Aubry 2012;Deveraux et al 2017), we propose a continuum finite elements model to simulate cell behaviour over the flat and micropatterned substrates coated with adhesive fibronectin. As mentioned above, our main objective is to depict the nucleus self-deformation as a function of the micropillared substrate geometry and the actin network around the nucleus itself.…”
Section: Modelling Of Cell-substrate Interactionmentioning
confidence: 64%
“…The contact force f ct automatically applies once the cell approaches the substrate, whether it is flat or micropillared, over a very thin layer corresponding to the superposition between the cell and the substrate. Then, it is approximated by a volume force as proposed in our previous work (Deveraux et al 2017). We employ here a penalization technique via the level set functions g flat and g mp which allow to measure the distance and the interpenetration between the cell and the substrates.…”
Section: The Contact Force Between the Cell And The Substratementioning
confidence: 99%
See 1 more Smart Citation
“…Overall, our data regarding both cell dynamics at very short scale and final cell morphology after passing through the constrictions raises the issue of the link between nuclear stiffness and plasticity. Recent experimental 29 and modeling 30 studies have shown that softer nuclei (i.e. Lamin A/C-deficient nuclei in the work of Cao et al) present a larger irreversible plastic deformation after being constricted than stiffer nuclei.…”
Section: Discussionmentioning
confidence: 97%
“…To be consistent with the observed values in live cell experiments, length, width, and thickness of the cell were chosen to be 40, 12, and 8 μm, respectively, and the bead embedding was set to be 38%, as the experimentally measured bead embedding was 36.3% (Supplementary Table 2). The thickness of cell membrane cortex 42 was set to be 0.25 μm. The nucleus was modeled as an elastic ellipsoid with its long axis as 12 μm and short axis as 7 μm.…”
Section: Methodsmentioning
confidence: 99%